Longitudinal analysis of a secondary BRCA2 mutation using digital droplet PCR. (20th November 2019) - Khalique, Saira; Pettitt, Stephen J; Kelly, Ger; Tunariu, Nina; Natrajan, Rachael; Banerjee, Susana; Lord, Christopher J
Abstract: Development of resistance to platinum and poly(ADP‐ribose) polymerase inhibitors via secondary BRCA gene mutations that restore functional homologous recombination has been observed in a number of cancer types. Here we report a case of somatic BRCA2 mutation in a patient with high grade serous ovarian carcinoma. A secondary mutation predicted to restore the BRCA2 open reading frame was detected at low frequency (2.3%) in whole exome sequencing of a peritoneal biopsy at disease progression after treatment that included carboplatin and olaparib. We used digital droplet PCR (ddPCR) to verify the presence and frequency of this mutation in the biopsy sample at progression and also used this approach to assess the presence of the secondary mutation in preceding biopsies at diagnosis and first relapse. We found no evidence for the secondary mutation being present prior to the final progression biopsy, suggesting that this mutation was acquired late in the course of treatment. ddPCR provides a sensitive and specific technique to investigate the presence of low frequency mutations in a time series of biopsies.